Uso de modelos moleculares por alunos de ensino médio : contribuições para o desenvolvimento de modelos mentais de conceitos químicos - Oliveira, Ricardo Castro de (Universidade Federal de São Carlos, 2012)
This study aimed to analyze the contribution of molecular models to the evolution process of the mental models of first grade high school students regarding the following chemical concepts: substance, reactants, products, rearrangement, Proust s Law, Lavoisier s Law, balancing, stoichiometry and submicroscopic representation of chemical reactions. The project involved the participation of 335 students and 06 teachers from three public schools in the region of São Carlos/SP. Data collection was performed in two stages: the first one took place at the schools during the 2011, school year, and the other occurred during a short course offered for the students, in the vacation period, at the Laboratory for Chemistry Teaching and Learning (LENAQ) of the University Federal of São Carlos/SP. Activities that addressed the concepts mentioned were elaborated and each student had an Atomlig® molecular model kit and a plastic balance that could be used to help solving the questions. Data were collected through written records, interviews and filming. It was found that most students (47.2%) showed a significant evolution of the mental models for the selected chemical concepts. A considerable portion (45.1%) showed an oscillation with respect to understanding of the concepts, while some students (7.4%) kept a constant performance and a minority (0.3%) showed a regression throughout the school year. The data allowed us to infer that, in general, students showed evidence of significant learning during the short course, highlighting the relevance of molecular models to the evolution process of student s mental models.
Use of molecular models by high school students: contributions to the development of mental models of chemical concepts
Keywords: Química - ensino; Material didático; Ensino médio; Aprendizagem; CIENCIAS EXATAS E DA TERRA::QUIMICA